PENGARUH KUALITAS PELAYANAN, CITRA MEREK, DAN LOKASI TERHADAP KEPUTUSAN MENGINAP DI HOTEL MERCURE JAKARTA GATOT SUBROTO - Dyah Ajeng Praptiningrum; Ricky Talumantak (GoAcademica Research dan Publishing, 2022)
This study aims to analyze and determine the effect of service quality, brand image, and location on the decision to stay at the Mercure Jakarta Gatot Subroto Hotel. The population in this study is the consumer of the Mercure Jakarta Hotel Gatot Subroto who has stayed at least 1 time. The data used in this study is primary data. The sample in this paper is 100 respondents at the Mercure Hotel Jakarta Gatot Subroto using accidental sampling technique. The research method used is quantitative and uses multiple linear regression analysis approach. The results of this study state that partially the Service Quality and Brand Image variables have no significant effect on the Decision to Stay at the Mercure Jakarta Gatot Subroto Hotel, while the Location Variable has a significant effect on the Decision to Stay at the Mercure Jakarta Gatot Subroto Hotel. And simultaneously the variables of Service Quality, Brand Image and Location have a significant effect on the dependent variable, namely the decision to stay.